Endurance and Resistance Training Affect High Fat Diet-Induced Increase of Ceramides, Inflammasome Expression, and Systemic Inflammation in Mice - Cornelia Mardare; Karsten Krüger; Gerhard Liebisch; Michael Seimetz; Aline Couturier; Robert Ringseis; Jochen Wilhelm; Norbert Weissmann; Klaus Eder; Frank-Christoph Mooren (Journal of Diabetes Research)
The study aimed to investigate the effects of differentiated exercise regimes on high fat-induced metabolic and inflammatory pathways. Mice were fed a standard diet (ST) or a high fat diet (HFD) and subjected to regular endurance training (ET) or resistance training (RT). After 10 weeks body weight, glucose tolerance, fatty acids (FAs), circulating ceramides, cytokines, and immunological mediators were determined. The HFD induced a significant increase in body weight and a disturbed glucose tolerance (p<0.05). An increase of plasma FA, ceramides, and inflammatory mediators in adipose tissue and serum was found (p<0.05). Both endurance and resistance training decreased body weight (p<0.05) and reduced serum ceramides (p<0.005). While RT attenuated the increase of NLRP-3 (RT) expression in adipose tissue, ET was effective in reducing TNF-α and IL-18 expression. Furthermore, ET reduced levels of MIP-1γ, while RT decreased levels of IL-18, MIP-1γ, Timp-1, and CD40 in serum (p<0.001), respectively. Although both exercise regimes improved glucose tolerance (p<0.001), ET was more effective than RT. These results suggest that exercise improves HFD-induced complications possibly through a reduction of ceramides, the reduction of inflammasome activation in adipose tissues, and a systemic downregulation of inflammatory cytokines.